A nonlinear decomposition analysis of the rural-urban disparities in tobacco use among women in sub-Saharan Africa - Richard Gyan Aboagye; Bright Opoku Ahinkorah; Irene Esi Donkoh; Joshua Okyere; Sanni Yaya (PLoS ONE, 2025)
Background Tobacco use remains a major public health challenge in sub-Saharan Africa, with significant gendered dimensions. Place of residence is an important determinant, as rural and urban contexts shape exposure, access, and consumption patterns. This study investigates rural–urban disparities in tobacco use among women in sub-Saharan Africa, with a focus on quantifying the relative contributions of socioeconomic factors. Methods We conducted a pooled cross-sectional analysis using nationally representative data from the most recent Demographic and Health Surveys (DHS) of 22 sub-Saharan African countries (2015–2022). The study sample included 350,536 women aged 15–49 years with complete data on tobacco use and relevant covariates. Tobacco use was defined as self-reported current use of cigarettes or other tobacco products. We employed a multivariate decomposition for non-linear response models to quantify the contributions of group differences in characteristics versus differences in how those characteristics affect an outcome. This technique partitions the observed rural–urban gap in tobacco use into two components: (1) endowment effects (compositional differences in characteristics such as education, household wealth, age, marital status, and employment) and (2) coefficient effects (differences in the influence of these characteristics on tobacco use between rural and urban women). Models adjusted for sampling weights and survey design effects to ensure representativeness. Results Compositional differences explained 167.48% of the rural–urban disparity in women’s tobacco use. Educational attainment and wealth index were the most significant contributors, both showing protective effects. If rural women’s education and wealth levels matched those of urban women, tobacco use prevalence would be reduced by 24.99% and 49.84%, respectively. Differences in coefficients accounted for −67.48% of the observed gap, with baseline differences in intercepts (−166.17%) driving most of this effect. These findings highlight both structural disadvantages and variations in behavioural responsiveness across residential settings. Conclusion The study demonstrates that rural–urban disparities in tobacco use among women are primarily shaped by inequalities in education and wealth. Interventions aimed at expanding educational opportunities and addressing poverty in rural communities could substantially reduce tobacco use. Additionally, tailored prevention and cessation strategies targeting women at both the lowest and highest ends of the socioeconomic spectrum are essential to mitigate disparities and advance tobacco control in sub-Saharan Africa.